MENGURAI AKAR ISU PENSIUN DINI GURU PENDIDIKAN AGAMA ISLAM DAN STRATEGI PEMERINTAH MALAYSIA DALAM MENGATASINYA - Jenny Ambiani; Nazir; Helmiati (STAI Pelabuhan Ratu, 2025)
The phenomenon of early retirement is alarming and not only affects the quality of education, but also creates a shortage of experienced teachers. This article aims to analyze the main factors driving teacher early retirement, focusing on excessive workload, administrative pressure, low levels of teacher welfare, and the role of government policy in responding to this issue. The results show that high workload, administrative tasks unrelated to teaching, leadership, and lack of support from the school administration are the main causes of early retirement. In addition, low teacher welfare, both physically and mentally, exacerbates the situation. The article concludes that policy interventions that support teacher welfare, workload reduction and school infrastructure improvement are needed to address this issue.